Prohibited means and methods of armed conflicts - Аракелян, Мінас Рамзесович; Аракелян, М. Р.; Аракелян, Минас Рамзесович; Arakelian, Minas R.; Бехруз, Хашматулла Набієвич; Бехруз, Х. Н.; Бехруз, Хашматулла Набиевич; Bekhruz, Khashmatulla N.; Ярова, Ліліана Вікторівна; Ярова, Л. В.; Яровая, Лилиана Викторовна; Yarova, Liliana V. (Universidad de la Amazonia, 2020)
The goal of this article is to analyze prohibited means and methods of armed conflicts under the International Humanitarian Law (IHL). Technological progress, the transformation of the nature of armed conflicts and the idea of the war based on terror are the main reasons why the list of prohibited means and methods of armed conflicts should be constantly updated. The main text of this article consists of three thematic blocks. The first block represents an excursion into the history and development of IHL. It outlines its division into two branches, the Geneva and Hague law. The second part consists of definitions and characteristics of basic terms such as means and methods of armed conflicts. Under the means of warfare it is understood weapons, military equipment and other means used to cause harm and defeat the enemy. Methods of warfare are the procedures for using certain means to suppress the troops of the opposing side and inflict losses on it at the very minimum acceptable level. The third part of the study is devoted to new methods and means of warfare, among which the author analyzes such phenomena as hybrid wars, cyberwar and the involvement of private military and security companies in military operations. Hybrid wars, widespread in the 21st century, raise very complex issues related to the classification of a conflict, as the line between the state of war and peace is blurring. Most often, information about the nature of third-party intervention is kept secret. Moreover, such a third party refuses to acknowledge its participation in hostilities. It is concluded that parties to hybrid wars are required to comply with international standards that limit the methods and means of warfare and protect their victims. The article examines the concepts of cyber war, identifies the main characteristics of this type of war. The main conclusion was made about the need of formation of new restrictive approaches regarding the prohibition of the use of cyber weapons. Another trend related to modern armed conflicts is the process of delegating the performance of traditional state functions by states in favor of private military and security companies. The conclusion is drawn on the need to develop international legal standards for the activities of private military and security companies within the UN.

Метою даної роботи є аналіз заборонених засобів і методів ведення збройних конфліктів відповідно до міжнародного гуманітарного права. Технічний прогрес, трансформація характеру збройних конфліктів і ідея терористичних війн є основними причинами, чому перелік заборонених засобів і методів ведення збройних конфліктів повинен постійно оновлюватися. Основний текст цієї статті складається з трьох тематичних блоків. Перший блок є екскурсом в історію і розвиток міжнародного гуманітарного права та містить характеристику двох його напрямів - Женевського і Гаазького права. Друга частина складається з визначень і характеристик основних термінів, таких як засоби і методи збройних конфліктів. Засоби ведення війни визначені як зброя, військова техніка, озброєння та інші засоби, що застосовуються для нанесення шкоди і поразки противнику, а методи ведення війни як порядок використання певних засобів з метою подолання військ противника і нанесення йому втрат на самому мінімальному допустимому рівні.Третя частина дослідження присвячена новим методам і засобам ведення війни, серед яких проаналізовані такі явища, як гібридні війни, кібервійни та залучення приватних військових і охоронних компаній у військові дії. Гібридні війни, які отримали широке поширення у XXI ст., викликали дуже складні питання, пов'язані з класифікацією того чи іншого конфлікту, оскільки ускладнили встановлення меж між станом війни і миру. Найчастіше інформація про характер втручання третьої сторонни у військові дії міститься у таємниці. Більш того, така третя сторона на практиці відмовляється визнавати свою участь у бойових діях. Зроблено висновок, що сторони в гібридних війнах зобов'язані дотримуватися міжнародних норм, що обмежують засоби ведення бойових дій і захищають жертв війни. У статті досліджено поняття кібервійни, визначено основні характеристики цього типу війни. Основний висновок зроблено про необхідність формування нових обмежувальних підходів щодо заборони використання кіберзброї. Ще однією тенденцією, пов'язаною із сучасними збройними конфліктами, є процес делегування виконання традиційних державних функцій державами на користь приватних військових і охоронних компаній. Зроблено висновок про необхідність розробки міжнародно-правових стандартів діяльності приватних військових і охоронних компаній в рамках ООН.

Целью данной работы является анализ запрещенных средств и методов ведения вооруженных конфликтов в соответствии с международным гуманитарным правом. Технический прогресс, трансформация характера вооруженных конфликтов и идея террористических войн являются основными причинами, почему перечень запрещенных средств и методов ведения вооруженных конфликтов должен постоянно обновляться. Основной текст этой статьи состоит из трех тематических блоков. Первый блок является экскурсом в историю и развитие международного гуманитарного права и содержит характеристику двух его направлений - Женевского и Гаагского права. Вторая часть состоит из определений и характеристик основных терминов, таких как средства и методы вооруженных конфликтов. Средства ведения войны определены как оружие, военная техника, вооружение и другие средства, применяемые для нанесения вреда и поражения противнику, а методы ведения войны как порядок использования определенных средств с целью преодоления войск противника и нанесения ему потерь на самом минимальном допустимом уровне.Третя часть исследования посвящена новым методам и средствам ведения войны, среди которых проанализированы такие явления, как гибридные войны, кибервойны и привлечения частных военных и охранных компаний в военные действия. Гибридные войны, получили широкое распространение в XXI в., вызвали очень сложные вопросы, связанные с классификацией того или иного конфликта, поскольку усложнили установление границ между состоянием войны и мира. Чаще всего информация о характере вмешательства третьей стороны в военные действия содержится в тайне. Более того, такая третья сторона на практике отказывается признавать свое участие в боевых действиях. Сделан вывод, что стороны в гибридных войнах обязаны соблюдать международные нормы, ограничивающие средства ведения боевых действий и защищают жертв войны. В статье исследовано понятие кибервойны, определены основные характеристики этого типа войны. Основной вывод сделан о необходимости формирования новых ограничительных подходов относительно запрета использования кибероружия. Еще одной тенденцией, связанной с современными вооруженными конфликтами, является процесс делегирования выполнения традиционных функций государствами в пользу частных военных и охранных компаний. Сделан вывод о необходимости разработки международно-правовых стандартов деятельности частных военных и охранных компаний в рамках ООН.
Arakelian M. Prohibited means and methods of armed conflicts / M. Arakelian, K. Bekhruz, L. Yarova // Amazonia Investiga. – V. 9 (26). – Universidad de la Amazonia, 2020. – Р. 349-355.
Keywords: аrmed conflicts; biological weapon; chemical weapon; combatants; cyberwar; hybrid warfare; International Humanitarian law (IHL); mines; nuclear weapon; Unmanned Air Vehicles; warfare; weapon; біологічна зброя; війна; гібридна війна; дрони; збройні конфлікти; зброя; кібервійна; комбатанти; міни; міжнародне гуманітарне право (МГП); хімічна зброя; ядерна зброя; биологическое оружие; война; гибридная война; дроны; вооруженные конфликты; оружие; кибервойна; комбатанты; мины; международное гуманитарное право (МГП); химическое оружие; ядерное оружие; Research Subject Categories::LAW/JURISPRUDENCE